2014
DOI: 10.1159/000356323
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Polysomnographic Assessment from Acute to Subacute Phase in Infratentorial versus Supratentorial Stroke

Abstract: Background: Regulation of sleep and sleep-related breathing resides in different brain structures. Vascular lesions can be expected to differ in their consequences on sleep depending on stroke topography. However, studies addressing the differences in sleep and sleep-related breathing depending on stroke topography are scarce. The aim of the present investigation was to compare the sleep and sleep-related breathing of patients with supratentorial versus infratentorial stroke. Methods: This study was part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Initial studies found no link between SDB and stroke topography. Population-based 5 and clinical 6 cohorts recently noted an association of SDB with brainstem stroke, suggesting that lower cranial nerve dysfunction aggravates SDB. The most common form of SDB is obstructive sleep apnea (OSA), which is caused by cessation of nasal flow due to upper airway collapse.…”
Section: Disturbed Sleep In Stroke Patientsmentioning
confidence: 99%
“…Initial studies found no link between SDB and stroke topography. Population-based 5 and clinical 6 cohorts recently noted an association of SDB with brainstem stroke, suggesting that lower cranial nerve dysfunction aggravates SDB. The most common form of SDB is obstructive sleep apnea (OSA), which is caused by cessation of nasal flow due to upper airway collapse.…”
Section: Disturbed Sleep In Stroke Patientsmentioning
confidence: 99%
“…Short events have previously been associated with increased all-cause mortality, which might connect short events to lower arousal threshold and elevated sympathetic tone [8]. Acute phase of stroke has been previously associated with deterioration of sleep quality [18,19]. Possible low arousal threshold combined with light and fragmented sleep could at least partially explain the observed short event durations.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have reported similar symptoms and disorders after both cortical and subcortical ischemic stroke [8,10,11]. Sleeprelated breathing disorders can be a consequence of stroke and represent an independent risk factor for cerebrovascular diseases [12,13]. Stroke-related sleep disturbances are very common during the acute phase and persist in 25% of the patients [12].…”
Section: Journal Of Geriatricsmentioning
confidence: 87%
“…Since the patients with an elevated PUI had relevant sleep disorders as well as significantly more vascular risk factors, the PST might be an important screening technique to identify a subgroup of patients with WML at high risk of vascular events. This result is crucial especially for patients with sleep apnea, since sleep-related breathing disorders themselves increase the risk of cardiovascular and cerebrovascular pathology [12,13]. Furthermore, the PST distinguished insomnia patients with PLMS from insomnia patients without PLMS, so the PLMS might further reduce sleep quality in insomnia patients [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation